Aspek Hukum Perencanaan Tata Ruang Kawasan Perkotaan di Indonesia - M. Zuhri (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: A City problem is very complicated; it is caused by the needs of human being life, which increases routinely. In solving that problem, it requires the availability solution through regulation. One of the regulations needed is through the City Region Spatial Planning. The people must obey that regulation. It is expected thst it could create environmental balancing, sustainability, and finally it can create   welfare and justice for people. Legal Aspect of Spatial Planning for City Space in Indonesia